Effectiveness of Early Detection by Social Cultural Units in Conflict Prevention Between Silat Colleges at Jombang Police - Yusriyadi, Riqy (Advances in Police Science Research Journal, 2024)
This research will focus on the operational activities of early detection in the form of intelligence investigations by the Satintelkam Polres Jombang to prevent conflicts between pencak silat organizations. This is due to the increasing cases of conflicts between pencak silat organizations in Jombang Regency. The concepts used include early detection, intelligence, intelligence investigation, conflict prevention, and operational intelligence management. The theories used in this research are competence theory, human needs theory, and work effectiveness theory. Additionally, this research also utilizes legal regulations such as Law Number 2 of 2002, Police Regulation Number 2 of 2021, and District Regulation Number 1 of 2023. The research results show that the competence of personnel in Unit Social Cultural Satintelkam is still not optimal. The underlying background of conflicts between martial arts schools lies in the egos of the members within the schools, community affiliations, fanaticism towards symbols, and insufficient supervision by leaders over members. Furthermore, the implementation of early detection in the Social Cultural Unit is still not effective. From the conducted research, it can be concluded that steps are needed to optimize the competence of personnel and the performance of intelligence investigations in Unit Social Cultural to be more effective. Consequently, Unit Social Cultural Satintelkam can make a greater contribution in handling conflicts between pencak silat organizations in the Jombang Regency area.